The Effectiveness of Group Guidance Services Based on Banjar Oral Culture in Improving Students' Politeness Behavior - Nur Kholifatun Nissa; Akhmad Rizkhi Ridhani; Muhammad Eka Prasetia (Indonesian Journal of Guidance and Counseling Studies, 2024)
Background: Politeness behaviour among students is an essential aspect of character education that supports academic and social development. Local cultural values, such as those found in Banjar oral traditions, can serve as a foundation for instilling positive behaviours in students. Objective: This study aimed to determine the effectiveness of group guidance services based on Banjar oral culture in improving the politeness behaviour of students at SMAN 1 Alalak. Method: The research was conducted at SMAN 1 Alalak in 2023 using a pre-experimental method with a one-group pretest-post-test design. Data on students' politeness behaviour were collected using a standardized behaviour scale and analysed using the Paired Sample T-test. Result: The analysis showed a significant increase in politeness behaviour scores after the implementation of the group guidance services. The Sig. (2-tailed) value was 0.000, which is less than the significance level of 0.05, indicating that the intervention had a statistically significant effect. Conclusion: Group guidance services grounded in Banjar oral culture are effective in enhancing students' politeness behaviour. The integration of cultural values into guidance practices strengthens character education efforts in schools. Contribution: This study contributes to the development of culturally-based guidance models and emphasizes the importance of local wisdom in shaping student character, offering a practical approach for educators to promote positive student behaviour.